Risk Factors for Overweight Among Students at SDN 104219 Tanjung Anom - Sibagariang, Eva Ellya; Hulu, Victor Trismanjaya; Ginting, Anabel Tesalonika BR (Open Access Health Scientific Journal, 2025)
Background: The increase in cases of malnutrition among elementary school children is caused by high-energy, low-fiber diets, inactive lifestyles, environments that encourage fast food consumption, and a lack of nutrition education. This study aims to analyze risk factors for overweight among elementary school students.Methods: This study used a cross-sectional design conducted on April 20-21, 2025, at SDN 104219 Tanjung Anom. The research subjects were all grades IV and V students, totaling 52 people, who were selected using the total sampling technique. The independent variables consisted of fast food, sweet food, snack food, fruit and vegetable consumption, and physical activity. The dependent variable was overweight. Food consumption data were collected using the 2×24-Hour Recall method (school days and weekends) to obtain a more accurate picture of average intake. Physical activity was measured with the Physical Activity Questionnaire for Children (PAQ-C). Data analysis using the Chi-square test and logistic regression.Results: Fast food consumption (p < 0.001; OR = 10.8; 95% CI = 2.512-46.423), consumption of sweets (p < 0.001; OR = 23.8; 95% CI = 4.383-126.670), snack consumption (p < 0.001; OR = 15.4; 95% CI = 2.898-25.959) has a significant association with overweight of school children. Fruit and vegetable consumption (p = 0.509; OR = 0.66; 95% CI = 0.187-2.302), physical activity (p = 0.238; OR = 0.47; 95% CI = 0.135-1.657) showed no significant association with overweight of school children.Conclusion: Eating fast food, sweet foods, and snacks more than three times a week is a risk factor for overweight in elementary school children.